Anterior urethral valves associated with hypospadias - Mahajan J; Ojha Sunita; Rao KLN (Wolters Kluwer Medknow Publications, 2007)
An association of coronal hypospadias with meatal stenosis and anterior urethral valves is described in this report. A combination of double obstruction in anterior urethra may overshadow the expression of proximal one.